Challenges and Prospects for Legal Regulation of Working Time (Connection Time) for Digital Platform Workers - Denis Novikov (Legal Issues in the Digital Age, 2025)
Digital platforms, transforming the labour market through crowdsourcing and multitasking, create legal challenges in regulating of working time, exacerbated by the inefficacy of traditional labour legislation. The formal autonomy of self-employed platform workers masks algorithmic control, where the absence of fixed shifts (slots) coexists with dependence on platform prescriptions and algorithms. The legal ambiguity of working time on digital platforms, which conflates active work with periods of online availability, leaves workers unprotected against digital control that disguises exploitation as market flexibility. To address the problems of platform-based work distribution and the practical inefficacy of classical regulatory approaches, the theoretical concept of connection time is proposed in the article. Unlike zero-hour contract, that masks the absence of guarantees through flexibility, and traditional normative limits on working hours, inapplicable to platform employment, connection time offers an alternative by integrating active and passive modes of online availability into a unified legal framework. Within this concept, the mere act of connecting to a platform is recognized as creating a mandatory measure of labour that restricts worker autonomy. Active connection time, linked to task performance, is governed by duration limits and payment guarantees, while passive connection time (waiting for orders, maintaining ratings, readiness for tasks) is acknowledged as labour activity requiring compensation for readiness, that restricts personal autonomy. The concept of connection time addresses the issue of multi-platform work as a phenomenon increasing risks of workplace accidents and occupational diseases. The proposed legal innovations are insufficient without a technological approach: states must implement algorithmic regulation and monitoring systems to automate control over connection time. Institutionalizing connection time will transform abstract norms into enforceable rules, eliminating risk asymmetry between platforms and workers, while establishing the state’s regulatory authority in platform employment.